Evading the Patronage Trap : Interest Representation in Mexico - Palmer-Rubin, Brian (Book collections on Project MUSE., 2022)
"Why have Latin American democracies proven unable to confront the structural inequalities that cripple their economies and stymie social mobility? Brian Palmer-Rubin contends that we may lay the blame on these countries’ systems of interest representation, which exhibit “biased pluralism,” a system in which the demands of organizations representing economic elites—especially large corporations—predominate. A more inclusive model of representation would not only require a more encompassing and empowered set of institutions to represent workers, but would also feature spaces for non-elite producers—such as farmers and small-business owners to have a say in sectoral economic policies. With analysis drawing on over 100 interviews, an original survey, and official government data, this book focuses on such organizations and develops an account of biased pluralism in developing countries typified by the centrality of patronage—discretionarily allocated state benefits. Rather than serving as conduits for demand-making about development models, political parties and interest organizations often broker state subsidies or social programs, augmenting the short-term income of beneficiaries, but doing little to improve their long-term economic prospects. When organizations become diverted into patronage politics, the economic demands of the masses go unheard in the policies that most affect their lives, and along the way, their economic interests go unrepresented."